Wap 2.0 development - Tull, Chris (Que, 2002)
This book is a comprehensive tutorial that is logically organized, up-to-date, and includes coverage of the most popular wireless programming language, WML. Readers create a working application, developing examples that build from one chapter to the next. With each chapter readers are learning, practicing, and building on required skills necessary not only for wireless development, but also programming in general. By the end of the book, readers will have created a wireless database application that allows them to view, enter, and delete information. The book provides a usable reference of summaries on all languages discussed within the book, as well as a comparison of the wireless devices, and different development tools on the market today. Chris Tull writes tutorials and technical articles each week for AnywhereYouGo.com to help developers further their expertise in creating wireless applications. An application consultant and freelance writer, his writing has appeared in numerous publications, including Texas Technology , inquiry.com, and Managing Automation . He is also an active member of the STC (Society of Technical Communication). Chris has been involved in emerging technologies since mid-1990. Early in his career, he worked at Caver-Morehead Systems, where he was responsible for the integration of DBMS systems for companies such as Hewlett-Packard, EDS, and Texas Instruments. He also produced technical documentation for the company.